Space, time, and man : a prehistorian's view - Clark, Grahame, 1907- (New York : Cambridge University Press, 1992)
Professor Grahame Clark, a distinguished prehistorian, describes how man has extended his understanding of time and space far beyond that of his primate forebears through technology, social organization and, above all, his capacity for abstract thought. Prehistorians have shown that even Palaeolithic people had long outstripped their forebears in comprehending time and space; and social anthropologists have documented preindustrial societies in which people were fully aware of these dimensions but were severely restricted by their social and cultural worlds. Evidence for more expanded horizons first appeared with those civilizations which controlled extensive territories and recorded their history to some extent in writing. The transition to modern times was marked above all with the advance of geographical discovery culminating in the circumnavigation of the world and by the growth of an ampler and more critical view of human history.
Today people are searching for explanations of what we know in terms of natural science. This involves looking beyond our world to outer space and seeking to understand our place in the cosmos.
1. From animal ecology to human history -- 2. Space in preliterate societies -- 3. Time in preliterate societies -- 4. Civilization and the expansion of space -- 5. Civilization and the deepening of historical time -- 6. Evolution and world prehistory -- 7. Extraterrestrial space and time -- 8. Epilogue.
Includes bibliographical references (p. 155-161) and index.
Keywords: Prehistoric peoples; Civilization, Ancient; Space and time; Social evolution